Survey on Performance analysis of an Enhanced AODV Routing Protocol (International Journal of Scientific Research and Management (IJSRM), 2015)
This Paper has proposed modified AODV protocol, which is designed to improve the performance of Mobile Ad Hoc networks. This paper describes the characteristics, working and deficiency of AODV routing protocols, and proposed idea of modifying AODV routing protocol (MAODV). Basic idea of developing the MAODV is to select the path with less congestion and avoiding the congested root so that less packet dropping may due to congestion in mobile ad hoc network